2018
DOI: 10.1007/s12011-018-1439-2
|View full text |Cite
|
Sign up to set email alerts
|

Sources and Levels of Trace Elements Influence Some Blood Parameters in Murrah Buffalo (Bubalus bubalis) Calves

Abstract: Sources of supplemental minerals in the diet of animals are of important significance. Bio-availability of organic sources is believed to be more in the body as compared to regularly used inorganic sources and hence environment-friendly due to reduced mineral excretion, which in turn reduces their requirements in the diet as well. Twenty-four male Murrah buffalo (Bubalus bubalis) calves (about 18-20 months of age and 318.54 ± 8.85 kg body weight) were divided randomly into four groups of six animals each. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Mineral and vitamin supplementation is associated with a reduction in the incidence of lameness in dairy cows. Improper mineral nutrition can also be a prerequisite for lameness [ 26 , 71 , 112 ], being mainly caused by a lack of calcium, phosphorus, zinc, copper, manganese, selenium, iodine, or sulphur amino acids [ 83 ]. Minerals play a considerable role in determining the structural strength of hooves due to their involvement in specific biochemical pathways that are associated with keratin synthesis [ 1 , 74 ].…”
Section: Effect Of Nutrition On Lameness and Laminitismentioning
confidence: 99%
See 1 more Smart Citation
“…Mineral and vitamin supplementation is associated with a reduction in the incidence of lameness in dairy cows. Improper mineral nutrition can also be a prerequisite for lameness [ 26 , 71 , 112 ], being mainly caused by a lack of calcium, phosphorus, zinc, copper, manganese, selenium, iodine, or sulphur amino acids [ 83 ]. Minerals play a considerable role in determining the structural strength of hooves due to their involvement in specific biochemical pathways that are associated with keratin synthesis [ 1 , 74 ].…”
Section: Effect Of Nutrition On Lameness and Laminitismentioning
confidence: 99%
“…Insufficient amounts of zinc, copper, and manganese promoted oxidative stress, increased incidence of cartilage disorders, and poor horn quality [ 27 ]. Copper bound in an organic amino acid complex is more bioavailable than inorganic sulphate sources [ 103 , 112 , 113 , 114 , 115 , 118 , 121 ], thereby improving the production of keratinized tissue [ 113 , 117 ], demonstrating a lower incidence of hoof disease in dairy cows fed organic forms of trace elements [ 113 ] and a reduction in the prevalence of lameness [ 27 ].…”
Section: Effect Of Nutrition On Lameness and Laminitismentioning
confidence: 99%
“…Mn has functions in skeletal system development, carbohydrate and lipid metabolism, and the innate immune response (Santamaria, 2008 ; Haase, 2018 ). Organic sources (glycine amino acid-chelated zinc, manganese, and copper) presented higher bioavailability compared with inorganic sources (zinc sulfate monohydrate, manganese sulfate monohydrate, and copper sulfate pentahydrate) in Murrah buffalo (Mudgal et al, 2019 ). In addition, previous studies have reported the application of Mn in sheep, poultry, and swine production.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was observed that hoof capsule and sole horn Mn levels were quite similar in the cattle group. Mudgal et al(33) reported that plasma Fe, Mn, Cu, and Zn levels in 18-20 months old male Anatolian buffaloes were 3.78, 0.85, 0.77, and 2.42 ppm, respectively.In healthy female buffaloes, serum Fe, Mn, Cu, and Zn concentrations were 3.2, 0.059, 0.53, and 3.24 µmol/L, respectively(34). Sun et al (11) evaluated the serum TE levels in cattle with different lameness scores and showed that the lowest serum Cr levels in cattle with the lowest lameness score (approximately 0.5 µg/g) and serum Cr level was the highest (approximately 4 µg/g) in cattle with the highest lameness score.…”
mentioning
confidence: 99%